Passively Q-Switched and Mode-Locked Fiber Laser Based on a Zeolitic Imidazolate Framework-67 Saturable Absorber - Wang, Pengpeng; Zhu, Cunguang (Frontiers in Physics, 2022)
Exploring new saturable absorber (SA) materials with excellent performance to achieve Q-switching and mode-locking operations is a hot topic in ultrafast laser research. The impressive specific surface areas, structural tunability, thermal and chemical stability of the zeolitic imidazolate framework (ZIF) materials make them promising candidates as high-performance SAs. In this work, we demonstrated the potential of the ZIF-67 SAs for ultrafast fiber laser applications. The nonlinear optical absorption characteristics of the ZIF-67 SAs at the telecommunication band were investigated by using the balanced twin-detector method. By incorporating the ZIF-67 SAs into the Er3+-doped fiber laser cavity, stable Q-switching operation and mode-locking operation were both achieved. The research results are essential for promoting the application of novel hybrid nanomaterials in ultrafast lasers.